Respostas
respondido por:
3
2x^2-6x=0
delta=b^2-4ac
delta=(-6)^2-4.2.0
delta=36-0
delta=36
x=-b-/+ raiz de delta/2a
x=-(-6)-6/2.2
x=6-6/4
x=0/4
x=0
x=-(-6)+6/2.2
x=6+6/4
x=12/4
x=3
delta=b^2-4ac
delta=(-6)^2-4.2.0
delta=36-0
delta=36
x=-b-/+ raiz de delta/2a
x=-(-6)-6/2.2
x=6-6/4
x=0/4
x=0
x=-(-6)+6/2.2
x=6+6/4
x=12/4
x=3
respondido por:
2
Resposta:
Explicação passo-a-passo:
2x² - 6x = 0
a = 2
b = (- 6)
c = 0
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás